Utility of Fine Needle Aspiration Cytology in Assessing Breast Cancer Biomarkers - Mutinda C. Kyama (Medical Research and Its Applications Vol. 3, 2024)
This chapter presents an overview of fine-needle aspiration cytology (FNAC) and its role in the evaluation of breast cancer biomarkers. Breast cancer is the most common cancer among women, accounting for 22% of all female cancers. In breast cancer, the overexpression of human epidermal growth factor receptor-2 (HER-2/neu) is a prognostic marker indicated for stratification of patients for HER-2/neu targeted therapies. The steroid hormonal receptors for estrogen receptor (ER) and progesterone receptor (PR) are markers with prognostic value in early-stage cancer of the breast and ER is predictive for response to hormonal therapies. Fine-needle aspiration cytology (FNAC), can provide enough cellular samples and evaluation of HER2, ER and PR expression patterns has relevant clinical application because the sample can be collected before surgery and help plan the management of breast cancer patients. Evaluation of HER2, ER and PR status in cytology samples has a lot of clinical relevance since the sample can be obtained prior to surgery and help plan management of patients with inoperable breast carcinoma. Previous studies have reported that immunocytochemistry performed on cell block is a feasible method for evaluation of ER, PR and HER-2/neu status in breast cancer, especially when the cellblock has adequate tumor cells.